2003
DOI: 10.1021/ie020698k
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Condensable Impurities in CO2/CH4 Gas Feeds on Carbon Molecular Sieve Hollow-Fiber Membranes

Abstract: The presence of vapor impurities in gas streams presents problems for both polymeric and carbon materials. For natural gas processing applications, it is suspected that condensable hydrocarbons can cause significant performance declines for polymer membranes. This paper investigates the effect of these condensable vapor impurities on the performance of carbon molecular sieve (CMS) hollow-fiber membranes. Toluene and n-heptane were separately used as representative aromatic and paraffinic impurities, respective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(19 citation statements)
references
References 30 publications
(83 reference statements)
1
18
0
Order By: Relevance
“…Zeolite is one of the most widely used porous inorganic fillers incorporated in MMMs for CO 2 /CH 4 separation. PSf/Matrimid® hollow‐fiber membranes exhibited a 50 % increase in selectivity by adding zeolite to its selective skin layers 17, 32. In comparison to neat polymers, addition of CMS to Matrimid® and Ultem® improved the membrane selectivity by 45 % and 40 %, respectively, for CO 2 /CH 4 systems 25.…”
Section: MMM Interpenetrated With Organic Fillersmentioning
confidence: 99%
“…Zeolite is one of the most widely used porous inorganic fillers incorporated in MMMs for CO 2 /CH 4 separation. PSf/Matrimid® hollow‐fiber membranes exhibited a 50 % increase in selectivity by adding zeolite to its selective skin layers 17, 32. In comparison to neat polymers, addition of CMS to Matrimid® and Ultem® improved the membrane selectivity by 45 % and 40 %, respectively, for CO 2 /CH 4 systems 25.…”
Section: MMM Interpenetrated With Organic Fillersmentioning
confidence: 99%
“…This is within the target cost range defined by the commercial benchmark (cellulose acetate) of $415 per m 3 /hr/bar. Based upon our economic model developed from several literature studies [1,26], in a hypothetical NG upgrading system treating 35 MMSCFD at 25% CO 2 , the cellulose acetate membrane cost represents about 30 to 40% of the total capital investment. Using the higher permeance CMS/C membrane data, the TCI could be reduced by about 12%.…”
Section: Economic Analysis For Ng Upgradingmentioning
confidence: 99%
“…The decrease in performance is very crucial in industrial applications and real gas mixture separation. Vu et al [2] have investigated the effect of condensable impurities on the performance of carbon molecular sieve hollow-fiber membranes in CO 2 /CH 4 separation applications. In this context, the experimental studies by Koros et al [3] suggested that competition of permeating components for Langmuir adsorption locations (or free volumes) in glassy membranes will mainly end up in a decrease in their permeability, selectivity and increased cost of operation.…”
Section: Introductionmentioning
confidence: 99%
“…Vu et al [10][11][12] have also investigated the effects of condensable impurities on the performance of CO 2 /CH 4 separation of hollow fiber molecular sieve membranes. Their results were compared with the results obtained from polyimide polymeric membranes.…”
Section: Introductionmentioning
confidence: 99%